PENERAPAN TEKNOLOGI SILASE JERAMI JAGUNG SEBAGAI PAKAN TERAK DI OPHIR NAGARI KOTO BARU KABUPATEN PASAMAN BARAT - Ferry Lismanto Syaiful; Yayuk Sri Utami (Jurnal Hilirisasi IPTEKS, 2020)
Feed is an absolute necessity that must be considered in raising livestock. Generally, in the dry season, farmers are constrained by the availability of challenging to obtain feed. On the other hand, during the corn harvest season in Jorong Ophir Nagari Koto Baru, West Pasaman Regency, the availability of corn straw is very abundant. Corn straw is very potential as a feed source, but its utilization is not optimal because its quality is still low. To improve the quality and benefits of corn straw, farmers need an easy and simple technology to improve feed quality, including corn straw silage technology. This activity aims to increase the knowledge and skills of breeders and farmers or the people of Jorong Ophir Nagari Koto Baru in the application of technology for making corn straw silage as animal feed. The training activities were carried out by Jorong Ophir, which involved farmers and the community. The method of activity is counseling, training, and evaluation. In this activity, participants were seen enthusiastically following the implementation of the activity. After implementing this activity, it was seen that there was an increase in community knowledge and understanding in the application of making corn straw silage as animal feed processing. Of course, farmers can optimize waste as relatively cheap animal feed. We hope that from this activity, there will be a sustainability program carried out by farmers to optimize quality feed for increasing livestock productivity.